The Relevance Between the Medina Charter and Pancasila as Products of Philosophy - Muh. Japri; Anir Syam Azisyah; Muh. Ilham; Muh. Natsir Siola (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Pancasila and the Medina Charter are two historical documents born from pluralistic societies as responses to the challenges of social integration. This study aims to analyze the philosophical values of the Medina Charter and Pancasila, as well as to identify their relevance and common ground as philosophical products. Using a qualitative research method with a philosophical approach (ontology, epistemology, and axiology), this study finds that both documents are not merely legal products but crystallizations of profound thought regarding the nature of statehood. Ontologically, both view society as a unified entity (ummah) that respects identity differences. Epistemologically, both originated from a synthesis of transcendental values (revelation/divinity) and sociological realities through a deliberative process. Axiologically, both uphold the values of justice, religious freedom, the rule of law, and humanity. The study concludes that Pancasila has strong philosophical relevance to the Medina Charter, offering a "middle path" model that is neither a secular nor a theocratic state. This confirms the compatibility of Islam with Indonesian nationalism and the importance of moderation narratives in contemporary politics.